2007
DOI: 10.1038/nrmicro1706
|View full text |Cite
|
Sign up to set email alerts
|

Friend and foe: the two faces of Xenorhabdus nematophila

Abstract: Comparisons of mutualistic and pathogenic relationships are necessary to decipher the common language of microorganism-host interactions, as well as the subtle differences in dialect that distinguish types of symbiosis. One avenue towards making such comparisons is to study a single organism that speaks both dialects, such as the gamma-proteobacterium Xenorhabdus nematophila. X. nematophila inhabits and influences the lives of two host animals, helping one to reproduce optimally while killing the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
187
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 189 publications
(199 citation statements)
references
References 114 publications
3
187
0
5
Order By: Relevance
“…Several studies have indicated that X. nematophila causes immunosupression at different levels 56 . The cellular response is dampened through the killing of haemocytes within 3 hours of infection, probably by the toxic effects of cytolysin, lipopolysaccharide, toxins and fimbrial subunits 56 . The humoral response can also be suppressed by repressing AMP gene expression through a mechanism that remains to be characterized 57 .…”
Section: Box 2 | Insect Immune Responsementioning
confidence: 99%
“…Several studies have indicated that X. nematophila causes immunosupression at different levels 56 . The cellular response is dampened through the killing of haemocytes within 3 hours of infection, probably by the toxic effects of cytolysin, lipopolysaccharide, toxins and fimbrial subunits 56 . The humoral response can also be suppressed by repressing AMP gene expression through a mechanism that remains to be characterized 57 .…”
Section: Box 2 | Insect Immune Responsementioning
confidence: 99%
“…This method was developed to study the pathogenicity of Xenorhabdus and Photorhabdus species, which typically associate with nematode vectors as a means to gain entry into the insect. Entomopathogenic nematodes typically infect larvae via natural digestive or respiratory openings, and release their symbiotic bacterial contents into the insect hemolymph (blood) shortly thereafter 10 . The injection method described here bypasses the need for a nematode vector, thus uncoupling the effects of bacteria and nematode on the insect.…”
mentioning
confidence: 99%
“…Humoral immune responses include the production of antimicrobial peptides that can lyse bacteria (47). In the insect hemocoel, bacterial survival depends on rapidly countering immunity and killing the host, and, indeed, X. nematophila can suppress insect immunity and produces virulence factors that contribute to insect host death (26,48). Preadaptive responses that prime Xenorhabdus expression of immunosuppressive activities and toxins while still within the IJ receptacle could provide a selective advantage.…”
Section: From the Ij To The Insectmentioning
confidence: 99%